KAMPANYE GREENPEACE DALAM MENJAGA EKOSISTEM TERUMBU KARANG (CORAL REEFS) DI PERAIRAN INDONESIA - Meylina Ayu Sapira; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study discusses one of contemporary issue in International Relations namely an environmental issue regarding the Greenpeace campaign program in caring Indonesia’s marine coral reef ecosystems. From 2017 to 2021, it is reported that 35,15% of Indonesia’s marine coral reefs are in poor condition. Although a number of efforts have been made to restore coral reefs, they are still too little compared to the destruction caused by humans. Hence, Greenpeace as one of the suitable NGO actively takes part in caring and protecting Indonesia’s marine coral reef ecosystems. This study uses a qualitative method to narrate the destruction of coral reefs phenomenon and to describe the progress of Greenpeace program in carrying out their roles to conserve coral reefs. In order to analyse this case, this study uses Non-Governmental Organization Theory and Pluralism approach.The findings of this study resulted in Greenpeace has been executing their roles as independent actor focusing on environmental issue, namely as a motivator, communicator, dynamisator and facilitator by holding a number of campaign programs in a number Indonesia’s National Park known with their greatest coral reefs diversity which takes place in Raja Ampat Island, Karimunjawa Island and Spemonde Island. Moreover, Greenpeace also conducts brand audit program and public discussion on InstagaramKeywords : INGO, Greenpeace, Ekosistem Terumbu Karang, Coral Reefs Ecosystem,Campaign Program